Stylistyka historyczna a historia języka - zakresy pokrewieństwa - KRZYSZTOF MAĆKOWIAK (Stylistyka, 2021)
Linguistic stylistics has been undergoing an intensive development. Its vividness is proved by, among other things, its inner divisions, which led to the appearance of divisio- nal disciplines (e.g. pragmatic stylistics, comparative stylistics, analytical stylistics). An important position among them is occupied by historical stylistics. It enters, though it had gained subjectivity, in multiple connections and dependencies with other linguistic disciplines. These connections operate in both directions.The opinion that the dilemmas connected with the stylistic analysis without the suffi- cient knowledge about the condition of the language is endangered by superficiality has XVIto be treated as a truism. Researchers of the contemporary stylistic reality gain the neces- sary Information conceming the systemie- and non-systemic properties of Polish from their own linguistic competence. The matter is morę complicated in case of historical ana- lysis. In this case there is a specific cognitive barrier a so-called time shade, which makes the perception of the text morę difficult. The suggestiveness of the stylistic elements also blurs. In order to overcome the mentioned problems, one has to apply the principles of the widely understood diachronic linguistics.Stylistics can, however, offer a lot to the history of language. Especially, when we treat the latter one as a sphere integrating and systemizing our whole knowledge about the past. Historical stylistic in such circumstances has to be placed lower in the hierarchy of scien- tific disciplines. It can precise our knowledge of the respective subsystems of speech (in principle we posses stylistic works, which refer to every fragment of the linguistic codę, though most place has been devoted to lexis, syntax and word-formation so far) or to wi- den Information from the area of sociolinguistics. A particular role of stylistics in the ma- king of historical-linguistic synthesis is based on supplying the descriptions of the main fimctional variations of the language. According to the binding theoretical instructions, a complex image of the history of Polish should also contain systematical data conceming their appearance and dynamics of development.